Factors Associated with Self-Medication during the COVID-19 Pandemic: A Cross-Sectional Study in Pakistan - Bakhtawar Chaudhry; Saiza Azhar; Shazia Jamshed; Jahanzaib Ahmed; Laiq-ur-Rehman Khan; Zahid Saeed; Melinda Madléna; Márió Gajdács; Abdur Rasheed (Tropical Medicine and Infectious Disease, 2022)
Self-medication (SM) is characterized by the procurement and use of medicines by bypassing primary healthcare services and without consulting a physician, usually to manage acute symptoms of self-diagnosed illnesses. Due to the limited availability of primary healthcare services and the anxiety associated with the COVID-19 pandemic, the compulsion to SM by the public has increased considerably. The study aimed to assess the characteristics, practices, and associated factors of SM by the public during the COVID-19 pandemic in Sargodha, Pakistan. χ2-tests and univariable analyses were conducted to explore the identification of characteristics and the potential contributing factors for SM during COVID-19, while multivariable logistic regression models were run to study the effect of variables that maintained a significant association. The study was performed during July–September 2021, with n = 460 questionnaires returned overall (response rate: 99.5%). The majority of respondents were males (58.7%, n = 270) who live in the periphery of the town (63.9%, n = 294), and most of the respondents belonged to the age group of 18–28 years (73.3%, n = 339). A large number, 46.1% (n = 212), of the participants were tested for COVID-19 during the pandemic, and among them, 34.3% (n = 158) practiced SM during the pandemic; the most common source of obtaining medicines was requesting them directly from a pharmacy (25.0%; n = 127). The chances of practicing SM for medical health professionals were 1.482 (p-value = 0.046) times greater than for non-medical health personnel. The likelihood of practicing SM in participants whose COVID-19 test was positive was 7.688 (p-value < 0.001) times more than who did not test for COVID-19. Allopathic medicines, acetaminophen (23.6%), azithromycin (14,9%), and cough syrups (13%), and over the counter (OTC) pharmaceuticals, vitamin oral supplements, such as Vitamin C (39.1%), folic acid (23.5%), and calcium (22.6%), were the most commonly consumed medicines and supplements, respectively; being a healthcare professional or having a COVID-test prior showed a significant association with the usage of Vitamin C (p < 0.05 in all cases). Respondents who mentioned unavailability of the physician and difficulty in travelling/reaching healthcare professionals were found 2.062-times (p-value = 0.004) and 1.862-times (p-value = 0.021) more likely to practice SM, respectively; SM due to fear of COVID was more common in individuals who had received COVID-tests prior (p = 0.004). Practices of SM were observed at alarming levels among our participants. Consciousness and understanding about the possible adverse effects of SM must be established and validated on a continuous level; in addition, on a commercial level, collaboration from pharmacists not to sell products (especially prescription-only medicines) without a certified prescription must be developed and implemented.